Restraint stress induces and exacerbates intestinal inflammation in interleukin-10 deficient mice - Koh, Seong-Joon (World J Gastroenterol, 2015)
AIM: To investigate the effects of restraint stress on chronic colitis in interleukin (IL)-10 deficient (IL-10(-/-)) mice. METHODS: The first experiment compared the effect of restraint stress on the development of intestinal inflammation in wild-type and IL-10(-/-) mice. Both wild-type and IL-10(-/-) mice were physically restrained in a well-ventilated, 50 cm(3) conical polypropylene tube for 2 h per day for three consecutive days. The second experiment was performed to assess the effect of restraint stress on exacerbation of colitis induced by piroxicam in IL-10(-/-) mice. The IL-10(-/-) mice were exposed to restraint stress for 2 h per day for 3 consecutive days, and then treated with piroxicam for 4 d at a dose of 200 ppm administered in the rodent chow. RESULTS: In the first experiment, none of the wild-type mice with or without restraint stress showed clinical and histopathological abnormality in the gut. However, IL-10(-/-) mice exposed to restraint stress exhibited histologically significant intestinal inflammation as compared to those without restraint stress. In the second experiment, restraint stress significantly reduced body weight and increased the severity of intestinal inflammation assessed by histopathologic grading in IL-10(-/-) mice. Colonic IL12p40 mRNA expression was strongly increased in mice exposed to restraint stress. CONCLUSION: This novel animal model could be useful in future study of psychological stress in the pathogenesis of inflammatory bowel disease.